Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar IPA - Emylia Gusti (Universitas Sebelas Maret, 2020)
Science learning is one of the learning activities that make people think more logically and systematically. Science learning also requires students to think critically, find problems around them and find solutions. The use of appropriate learning models will be able to train students to think critically and logically. The purpose of this study is to describe the concept of the Problem Based Learning model, the nature of science and its learning and the results of the application of the Problem Based Learning model in science learning. The result of this study is the improvement of science learning outcomes by applying the Problem Based Learning model.